(3GdJfejI GdGbJUGOjI (B:s (3OQGSGJ fXQjI h JWHjbjI (B/s - (3YLejI, eMeO YHO GdYRjRs; (3YWjI, fGUa GjeGf s; (3fLG, Ydj YHO GdhgGHs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYI ddfTQ(B, s, 2006)
(3eaghe hNUGFU GdJNJa (B-(3NUGFU GdJNda(B--(3ebGjjS Gdfeh GdGbJUGOj(B-(3fXQjGJ hGSJQGJLjI GdJfejI GdGbJUGOjI(B--(3Jehjd GdJfejI GdGbJUGOjIGdTQcGJ eJYOOI GdLfSjGJ GdGUdGM GdGbJUGOj aj eUQ(B-(3feGPL GdGeJMGfGJs
Keywords: (3GdJfejI GdGbJUGOjIs; (3GdSjGSI GdGbJUGOjIs; (3Gdfeh GdGbJUGOjs